SUITABILITY OF RICE HUSK ASH MOULD ADDITIVE FOR THIN WALL DUCTILE IRON GRAPHITE CHARACTERISTICS (Nigerian Journal of Technology, 2018)
Thin wall ductile iron (TWDI) components are used in automobile and related sectors owing to weight savings without sacrificing functional properties. However, its application is hampered by low ductility owing to carbide precipitation and poor nodule characteristics in as-cast structure. In this study, mould thermal characteristics are adjusted using rice husk ash (RHA). Green sand was blended with 1-6 wt. % RHA to produce moulds for casting of 4 mm TWDIs, samples obtained were subjected to microstructural (Optical, SEM and EDS), hardness and strength analyzes. Elemental composition of carbide precipitates showed iron and carbon. Nodularity ratings > 90%, nodule count >1000 nodules/mm2 and strength of 596 MPa were observed in samples cast in 4 wt. % RHA sand mix. Ductility of 6.1 occurred in 6 wt. % RHA/sand mix. The sand-RHA mix offers cooling rate control, reduction of precipitation of deleterious carbides and superior graphite characteristics in 4 mm TWDI castings.http://dx.doi.org/10.4314/njt.v37i4.19